Empirical analysis and strategy suggestions on the value-added capacity of photovoltaic industry value chain in China. (1st August 2019) - Liu, Jicheng; Lin, Xiangmin
Abstract: Energy is the foundation and driving force of modernization. Renewable energy has been developed with the help of global environmental awareness. In recent years, supported by the relevant national industrial policies, China's photovoltaic market has developed rapidly and its production capacity is huge. However, the core of supporting the sustainable development of an industry lies in the continuous appreciation of the value of itself. In order to correctly understand the status quo and problems of PV industry value chain in China, based on the "Smile Curve" theory, taking the gross profit rate of PV industry listed companies as sample variables from 2015 to 2017, the research finds that its value chain shows a gradually deepening smile. And to explore the extent to which gross profit margin is affected by various factors, 15 variables are selected from six aspects: internal innovation power, growth potential, profitability, operational efficiency, scale strength and external environment, the Stepwise Regression method is used to determine the optimal model first. Further use Principal Component Analysis to confirm the motivations affecting the value-added of listed companies in the PV industry in the upper, middle and down reaches. The results indicate that only 6 variables have significant effects on the gross profit margin of the PV industry value chain, and there are big diversities in the main influencing factors of the value-added capacity of PV companies in different links, so they should seek their own value-added breakthroughs. Highlights: China's PV industry value chain conforms to the "smile curve" form. The profitability can significantly influence the value of the entire industry. Innovation is the key factor to the upper and downstream PV companies' value added. The key factor to midstream PV companies' value added is operational efficiency. Company's scale and external environment have synergistic effects on the value added.